Therapeutic Potential of Anti-Interferon α Vaccination on SjS-Related Features in the MRL/lpr Autoimmune Mouse Model - Killian, Martin; Colaone, Fabien; Haumont, Philippe; Nicco, Carole; Cerles, Olivier; Chouzenoux, Sandrine; Cathébras, Pascal; Rochereau, Nicolas; Chanut, Blandine; Thomas, Mireille; Laroche, Norbert; Forest, Fabien; et al. (Frontiers in Immunology, 2021)
Sjögren’s syndrome (SjS) is a frequent systemic autoimmune disease responsible for a major decrease in patients’ quality of life, potentially leading to life-threatening conditions while facing an unmet therapeutic need. Hence, we assessed the immunogenicity, efficacy, and tolerance of IFN-Kinoid (IFN-K), an anti-IFNα vaccination strategy, in a well-known mouse model of systemic autoimmunity with SjS-like features: MRL/MpJ-Faslpr/lpr (MRL/lpr) mice. Two cohorts (with ISA51 or SWE01 as adjuvants) of 26 female MRL/lpr were divided in parallel groups, “controls” (not treated, PBS and Keyhole Limpet Hemocyanin [KLH] groups) or “IFN-K” and followed up for 122 days. Eight-week-old mice received intra-muscular injections (days 0, 7, 28, 56 and 84) of PBS, KLH or IFN-K, emulsified in the appropriate adjuvant, and blood samples were serially collected. At sacrifice, surviving mice were euthanized and their organs were harvested for histopathological analysis (focus score in salivary/lacrimal glands) and IFN signature evaluation. SjS-like features were monitored. IFN-K induced a disease-modifying polyclonal anti-IFNα antibody response in all treated mice with high IFNα neutralization capacities, type 1 IFN signature’s reduction and disease features’ (ocular and oral sicca syndrome, neuropathy, focus score, glandular production of BAFF) improvement, as reflected by the decrease in Murine Sjögren’s Syndrome Disease Activity Index (MuSSDAI) modelled on EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI). No adverse effects were observed. We herein report on the strong efficacy of an innovative anti-IFNα vaccination strategy in a mouse model of SjS, paving the way for further clinical development (a phase IIb trial has just been completed in systemic lupus erythematosus with promising results).